EFS: an ensemble feature selection tool implemented as R-package and web-application - Neumann, Ursula (BioData Min, 2017)
BACKGROUND: Feature selection methods aim at identifying a subset of features that improve the prediction performance of subsequent classification models and thereby also simplify their interpretability. Preceding studies demonstrated that single feature selection methods can have specific biases, whereas an ensemble feature selection has the advantage to alleviate and compensate for these biases. RESULTS: The software EFS (Ensemble Feature Selection) makes use of multiple feature selection methods and combines their normalized outputs to a quantitative ensemble importance. Currently, eight different feature selection methods have been integrated in EFS, which can be used separately or combined in an ensemble. CONCLUSION: EFS identifies relevant features while compensating specific biases of single methods due to an ensemble approach. Thereby, EFS can improve the prediction accuracy and interpretability in subsequent binary classification models. AVAILABILITY: EFS can be downloaded as an R-package from CRAN or used via a web application at http://EFS.heiderlab.de.